Adaptasi Beberapa Galur Harapan Padi Sawah Untuk Menggantikan Varietas Ciherang di Provinsi Bali - Aryawati, Sagung Ayu Nyoman; Safitri, Heni; Kamandalu, Anak Agung Ngurah Bagus; Sunanjaya, Wayan; Kumala Sari, Anela Retna (Jurnal Penelitian Pertanian Tanaman Pangan, 2020)
The stages of assembling new superior varieties are the adaptation test lines of hope that will be proposed. Adaptation test was carried out in SubakBengkel, Tabanan Regency and SubakBatanWani, Badung Regency, Bali in 2018. The purpose of this study was to determine the agronomic performance of some rice lines in the two locations in the Province of Bali. The study used a randomized block design (RBD) with four replications. Data were analyzed using SAS and DMRT applications.The results of the analysis showed that the lines of hope that were tried had a significant effect on all plant parameters observed. The highest rice productivity was produced by the BP20797d-SKI-1-2-7-1 line of hope, which was 9.20 tons GKG h-1, more 4.78 and 7.38% compared to Ciherang and Inpari 33 varieties.Â